THE CASE OF THE REPUBLIC OF KAZAKHSTAN IN MATTERS OF PROTECTING CITIZENS’ RIGHTS THROUGH VARIOUS HUMAN RIGHTS AND METHODS AND MECHANISMS. HOW DOES KAZAKHSTAN COPE WITH IT? - Aueshova B.T.; Tulegenov D.E.; Zhumatai M.K.; Tagaibekova N.P (Modern Scientific Technology, 2025)
This article examines the case of the Republic of Kazakhstan in protecting citizens' rights through various human rights methods and mechanisms. It analyzes Kazakhstan's legal framework, institutional arrangements, and practical implementation of human rights standards, assessing the country's progress and ongoing challenges. The abstract considers Kazakhstan's engagement with international human rights treaties and mechanisms, the role of national human rights institutions, and the activities of civil society organizations in promoting and protecting human rights. It also addresses specific human rights issues in Kazakhstan, such as freedom of expression, assembly, and association, the rights of vulnerable groups, and access to justice. Finally, the abstract offers recommendations for strengthening human rights protection in Kazakhstan, emphasizing the importance of government commitment, independent monitoring, and effective remedies for human rights violations